Exploration of Implementation for Countermeasures Against Tuberculosis in Tabanan District: A Qualitative Study - Ni Wayan Restuti Handayani; I Gusti Mas Rwa Jayantiari; Ni Nengah Adiyaryani; Ani Susiani (Postgraduate, University of Mataram, 2023)
The achievement target for accelerating TB control in Bali Province and Tabanan Regency has not shown results that meet the target, which can have negative impacts in the form of delays in diagnosis and death in sufferers. This study aims to explore the implementation of tuberculosis control in Tabanan district, Bali Province. The study used a qualitative approach with in-depth interviews and focus group discussions (FGD) with regulators, program implementers, and other stakeholders, with a total of 25 respondents. The result of this study demonstrates that the integration of tuberculosis prevention implementation recommendations from the center to the Tabanan Regency Public Health Center is well established. The local government has allocated funds based on the number of tuberculosis elimination targets achieved in each health center. However, there was a misalignment between the guidelines and their execution in the Public Health Center. This is due to the lack of regional regulations that precisely outline the initiatives described in the center's guidelines. If this trend continues, tuberculosis control efforts will not be as effective as hoped. As a result, complete support is expected due to strong and explicit policies, as well as cross-sector cooperation, to ensure the program's success.